PERAN GURU DALAM MENINGKATKAN MINAT MEMPELAJARI BAHASA ARAB BAGI PESERTA DIDIK MADRASAH IBTIDAIYAH MUHAMMADIYAH - Nismawati Nismawati; Mahyudin Ritonga; Aguswan Rasyid (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Arabic is one of the compulsory subjects for Muhammadiyah educational institutions, this is reflected in the name of ismuba subjects (al-Islam Kemuhammadiyahan and Arabic). In reality, among many students who have a low interest in attending Arabic lessons, therefore it takes real steps for teachers to increase the interest of learners in learning Arabic. This research is designed with qualitative approach, the selection of this method is due to the nature of data in the form of words, sentences and reality requires in-depth analysis that is not only in the form of numbers, research data obtained through observation, interviews and documentation studies, analysis used as qualitatively starting from data reduction, data classification, and conclusion drawing. The results of the study can be revealed that Arabic teachers play a role in the interest of learners, the role is shown to be seen in the form of motivators, facilitators, mediators and innovators, the functioning of these four roles has an impact on increasing the interest of didi participants in MIM Pakasai to learn Arabic.